Methods for Cultivating Students' Personality and Morals Through Islamic Religious Education - Kurniati, Nia; El-Yunusi, Muhammad Yusron Maulana (Bulletin of Science, Technology and Society, 2023)
Islamic Religious Education (PAI) has a central role in shaping students' personality and morals. This study aims to formulate effective strategies in fostering students' personality and morals through Islamic education. The research methods used are literature analysis and case studies. In this study, the method used is a qualitative approach. The population of this study was addressed to Islamic Religious Education Teachers (GPAI) in shaping the character (char¬acter building) of students at MA Zainul Ulum BKL. The study highlighted the need for the integration of Islamic religious values in every aspect of education, rather than just as separate subjects. One of the main strategies is to develop a well-rounded curriculum, covering aspects of students' daily lives and encouraging the application of Islamic moral values in their actions. In addition, the role of teachers in guiding and providing role models is very important. They need to understand and internalize Islamic moral values, so they can convey them clearly to students and create a learning environment that supports good character building. The use of interactive and applicable learning methods is also proposed so that students can experience Islamic values in real-life situations.